Development and evaluation of polycrystalline cadmium telluride dosimeters for accurate quality assurance in radiation therapy. (12th February 2016) - Oh, K.; Han, M.; Kim, K.; Heo, Y.; Moon, C.; Park, S.; Nam, S.
Abstract: For quality assurance in radiation therapy, several types of dosimeters are used such as ionization chambers, radiographic films, thermo-luminescent dosimeter (TLD), and semiconductor dosimeters. Among them, semiconductor dosimeters are particularly useful for in vivo dosimeters or high dose gradient area such as the penumbra region because they are more sensitive and smaller in size compared to typical dosimeters. In this study, we developed and evaluated Cadmium Telluride (CdTe) dosimeters, one of the most promising semiconductor dosimeters due to their high quantum efficiency and charge collection efficiency. Such CdTe dosimeters include single crystal form and polycrystalline form depending upon the fabrication process. Both types of CdTe dosimeters are commercially available, but only the polycrystalline form is suitable for radiation dosimeters, since it is less affected by volumetric effect and energy dependence. To develop and evaluate polycrystalline CdTe dosimeters, polycrystalline CdTe films were prepared by thermal evaporation. After that, CdTeO 3 layer, thin oxide layer, was deposited on top of the CdTe film by RF sputtering to improve charge carrier transport properties and to reduce leakage current. Also, the CdTeO 3 layer which acts as a passivation layer help the dosimeter to reduce their sensitivity changes with repeated use due to radiation damage. Finally, the top and bottom electrodes, In/Ti and Pt, were used to have Schottky contact. Subsequently, the electrical properties under high energy photon beams from linear accelerator (LINAC), such as response coincidence, dose linearity, dose rate dependence, reproducibility, and percentage depth dose, were measured to evaluate polycrystalline CdTe dosimeters. In addition, we compared the experimental data of the dosimeter fabricated in this study with those of the silicon diode dosimeter and Thimble ionization chamber which widely used in routine dosimetry system and dose measurements for radiation therapy.